Repositioning the Role of the Church in to Eradicate Poverty, Enlightenment Congregation, and Developing Peaceful Living in the Context of Pluralism - Nainggolan, Daniel Maniur (Journal of Social Science and Education Research, 2024)
The task of the church in the contemporary Indonesian context demands a repositioning of the church's role to be relevant and transformative. This article explores the repositioning of the role of the church in three main dimensions: alleviating poverty, congregation educating, and developing peaceful living in a plural context, with an emphasis on practical innovations that can be adopted according to social, economic and political dynamics in 2024. This innovative approach will be focused on developing the creative economy, using digital technology, increasing digital literacy, and transforming learning through online platforms, and. Through a theological approach and contextual analysis, this article identifies challenges, opportunities and strategies that the church can implement in carrying out its mission holistically.